2014
DOI: 10.3329/jbau.v12i1.21242
|View full text |Cite
|
Sign up to set email alerts
|

Yield and nutrient uptake by wheat as influenced by integrated use of manures and fertilizers

Abstract: ) were found in T0 (Control). The NPKS uptake by wheat was markedly influenced by combined use of manures and fertilizers and the treatment T3 demonstrated superior performance to other treatments. So the treatment T3 comprising poultry manure in combination with chemical fertilizers on IPNS basis was found to be the best combination of manures and fertilizers for obtaining the maximum yield and quality of wheat at BAU farm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
4
6
0
Order By: Relevance
“…The increase in grain yield over control ranged from 51.44 to 69.72% where the highest increase was obtained in T 3 and the lowest one was obtained in T 5 FP [farmers' practices] as shown in Table 3. These results are in agreement with Islam et al (2014) who reported that combined application of manures and fertilizers increased the grain and straw yield of wheat. Malika et al (2015) and Liza et al (2014) also support the findings of the present study.…”
Section: Grain Yieldsupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in grain yield over control ranged from 51.44 to 69.72% where the highest increase was obtained in T 3 and the lowest one was obtained in T 5 FP [farmers' practices] as shown in Table 3. These results are in agreement with Islam et al (2014) who reported that combined application of manures and fertilizers increased the grain and straw yield of wheat. Malika et al (2015) and Liza et al (2014) also support the findings of the present study.…”
Section: Grain Yieldsupporting
confidence: 93%
“…These findings are well corroborated with that of Malika et al (2015), Islam et al (2014), and Akter et al (2012) who reported that integrated use of manures and fertilizers increased the grain and straw yield of rice and wheat. …”
Section: Straw Yieldsupporting
confidence: 87%
See 1 more Smart Citation
“…However, when combining urea with non-digested or digested manure crop biomass yield has increased significantly compared with application of sole urea or manure. The benefit of combining manures with mineral fertilizer has been reported in several studies where they confirmed this strategy yielded higher wheat biomass (Islam et al, 2014;Kearney et al, 2012;Kidinda et al, 2015). Because nutrient in mineral fertilizer will be available for the crop at application, while the organically bound nutrients in the manure would be released slowly, benefitting the crop during growing period.…”
Section: Root Straw Ears and Total Biomassmentioning
confidence: 79%
“…The current result is also parallel with the finding of [27] who shares the same opinion after analyzing the financial data of fertilizer use in cotton. Therefore, the present study revealed that combined use of PK under constant value of N fertilizer is better in economic terms for maximum sorghum production [28][29][30][31][32].…”
Section: Economics Of Fertilizer Usementioning
confidence: 99%